DIAGNOSTIC ACCURACY AND RELIABILITY OF DIRECT OPHTHALMOSCOPY COMPARED TO NON-MYDRIATIC RETINAL PHOTOGRAPHY FOR DIABETIC RETINOPATHY SCREENING - Athar Habib; Jahan Zeb; Mariam Sana Ullah; Muhammad Ahmad Raza; Sidra Ghazanfar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To compare the diagnostic accuracy and reliability of Direct Ophthalmoscopy versus Non-Mydriatic Retinal Photography in detecting diabetic retinopathyMaterial and Method: This was a comparative cross-sectional research conducted at Department of Optometry, University of Lahore Teaching Hospital, Lahore using purposive sampling and non-probability sampling. The study was conducted from January 2022 To September 2022. Every patient had a standard eye exam, including best corrected refraction and visual functions assessment, and their results were recorded in a database. An optometrist (Optometrist A) performed the initial screening without dilation of the pupil. With a Non Mydriatic fundus camera, two 45 degree retinal pictures were captured: one from the center to the macula and the other from the center to the optic disc. Following evaluation, the patient was informed about the possibility of temporary blurred vision and was advised not to drive after giving their agreeing for pupil dilatation.Results: Using NMFC without dilating the pupil, direct ophthalmoscope (DO) following pupil dilation, and a slit lamp with Volk's lens, 860 eyes of 430 people with type 2 diabetes were examined for DR. The slit lamp examination results served as a baseline against which to compare the results of NMFC. There were 93 (10.8%) non-readable fundi using biomicroscopy, 176 (20.4%) with NMFC, and 135(15.6%) with DO. Table 1 shows that the number of cases of diabetic retinopathy (DR) identified by slit lamp was 189 (21.9%), NMFC was 150 (17.4%), and direct ophthalmoscopy was 117 (13.6%).Conclusion: Non-mydriatic retinal photography is more reliable and accurate than direct ophthalmoscopy for the detection of diabetic retinopathy. The selection of these techniques, however, may be contingent upon variables including the accessibility of resources, the configuration of the screening program, and the particular requirements of the target population.